A Study of Event-Related Potentials during Monaural and Bilateral Hearing in Single-Sided Deaf Cochlear Implant Users - Voola, M.; Nguyen, A.T.; Wedekind, A.; Marinovic, Welber; Rajan, G.; Tavora-Vieira, Deyse (2023)
Objectives: Single-sided deafness (SSD) is characterized by a profoundly deaf ear and normal hearing in the contralateral ear. A cochlear implant (CI) is the only method to restore functional hearing in a profoundly deaf ear. In a previous study, we identified that the cortical processing of a CI signal differs from the normal-hearing ear (NHE) when directly compared using an auditory oddball paradigm consisting of pure tones. However, exactly how the brain integrates the electrical and acoustic signal is not well investigated. This study aims to understand how the provision of the CI in combination with the NHE may improve SSD CI users' ability to discriminate and evaluate auditory stimuli. Design: Electroencephalography from 10 SSD-CI participants (4 participated in the previous pure-Tone study) were recorded during a semantic acoustic oddball task, where they were required to discriminate between odd and even numbers. Stimuli were presented in four hearing conditions: directly through the CI, directly to the NHE, or in free field with the CI switched on and off. We examined task-performance (response time and accuracy) and measured N1, P2, N2N4, and P3b event-related brain potentials (ERPs) linked to the detection, discrimination, and evaluation of task relevant stimuli. Sound localization and speech in noise comprehension was also examined. Results: In direct presentation, task performance was superior during NHE compared with CI (shorter and less varied reaction times [∼720 versus ∼842 msec], higher target accuracy [∼93 versus ∼70%]) and early neural responses (N1 and P2) were enhanced for NHE suggesting greater signal saliency. However, the size of N2N4 and P3b target-standard effects did not differ significantly between NHE and CI. In free field, target accuracy was similarly high with the CI (FF-On) and without the CI (FF-Off) (∼95%), with some evidence of CI interference during FF-On (more variable and slightly but significantly delayed reaction times [∼737 versus ∼709 msec]). Early neural responses and late effects were also greater during FF-On. Performance on sound localization and speech in noise comprehension (SCINNHEconfiguration only) was significantly greater during FF-On. Conclusions: Both behavioral and neural responses in the semantic oddball task were sensitive to CI in both direct and free-field presentations. Direct conditions revealed that participants could perform the task with the CI alone, although performance was suboptimal and early neural responses were reduced when compared with the NHE. For free-field, the addition of the CI was associated with enhanced early and late neural responses, but this did not result in improved task performance. Enhanced neural responses show that the additional input from the CI is modulating relevant perceptual and cognitive processes, but the benefit of binaural hearing on behavior may not be realized in simple oddball tasks which can be adequately performed with the NHE. Future studies interested in binaural hearing should examine performance under noisy conditions and/or use spatial cues to allow headroom for the measurement of binaural benefit.